A Prediction Model for Collision Damage Considering the Coupling Effect of Wedge-Shaped Bow and Side Structures - Yanjie Zhao; Zisheng Lin; Yichi Zhang; Yuchao Yuan; Tongtong Guo (Journal of Marine Science and Engineering, 2026)
The prediction model for collision damage to a ship’s side structure plays a crucial role in the design phase. In traditional analytical methods, the bow of the striking ship is often simplified as a rigid body, with the majority of studies focusing on spherical or ellipsoidal bows. This paper focuses on wedge-shaped bows. First, numerical simulation analysis reveals that when the stiffness of the striking ship’s bow is relatively close to that of the struck ship’s side structure, accounting for the elastic–plastic deformation of the bow significantly affects the prediction results of collision damage to the struck ship. Building upon the rigid-body analytical prediction model (RAPM), further consideration of the elastic–plastic deformation of the striking ship’s bow leads to the development of a prediction model that accounts for the coupled collision damage process between the bow and the side structure (CDPM). Comparisons with simulation results and predictions from RAPM demonstrate that CDPM captures the physical process of collision damage more accurately, thereby proving the superiority of this approach over RAPM.